2020
DOI: 10.4111/icu.2020.61.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sterile pyuria as a prognosticbiomarker for intravesical recurrence in upperurinary tract urothelial carcinoma

Abstract: Purpose: To evaluate if preoperative sterile pyuria can be a prognostic factor for intravesical recurrence (IVR) and overall survival (OS) in patients with upper tract urothelial carcinoma (UTUC) undergoing surgery. Materials and Methods: We retrospectively reviewed the medical records of patients who were diagnosed with UTUC from October 2003 to December 2016 at Korea University Medical Center. Sterile pyuria was defined as urine containing five or more white blood cells per high-power field in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Four studies in our systematic review compared the effect of diabetes on IVR in UTUC patients after RNU (16,18,20,22). Jeon et al (18) and Lin et al (20) found that diabetes increases IVR in UTUC patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Four studies in our systematic review compared the effect of diabetes on IVR in UTUC patients after RNU (16,18,20,22). Jeon et al (18) and Lin et al (20) found that diabetes increases IVR in UTUC patients.…”
Section: Discussionmentioning
confidence: 97%
“…We initially identified 672 studies from the three databases mentioned above. Ten studies were ultimately included in this meta-analysis based on our inclusion and exclusion criteria (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). A total of 12,865 patients had UTUC, and 2045 (15.9%) had diabetes.…”
Section: Literature Screening and Quality Assessmentmentioning
confidence: 99%
“…This study has several limitations. The definition of pyuria is not objective and varies in the literature [12,28]. Moreover, pyuria is associated with numerous conditions such as infection, autoimmune disease and TURBT itself [29]; thus, we need to interpret the results of this study cautiously.…”
Section: Discussionmentioning
confidence: 98%
“…BCG unresponsiveness was defined as BCG refractory or BCG relapse with adequate BCG treatment [4]. Pyuria was defined as the presence of five or more white blood cells in a urine sample, as observed with a high-power field [12]. A tumour size of >3 cm was considered a large tumour.…”
Section: Patient Selection and Cohort Follow-up Protocolsmentioning
confidence: 99%
“…Interestingly, also postoperative pyuria was described as a negative prognostic factor in patients with bladder cancer [ 17 , 18 ]. Regarding upper urinary tract urothelial carcinoma, the impact of preoperative pyuria on the risk of bladder recurrence is uncertain due to conflicting results of published studies [ 19 , 20 , 21 ]. The mechanism by which pyuria can impact patients’ prognosis is not clear.…”
Section: Discussionmentioning
confidence: 99%